Setting Sosial Keagamaan dan Politik dalam Wacana Penerbitan Buku - Tedi, Enjang (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2018)
The main focus of the research is to reveal social setting of religious and politics in the discource of publishing Mizan’s books during 1983 to 1998 especially in implementing it’s vision and mission . The method of this research is qualitative research based on the library research with the primary source of data are interview and documentations. The data of the research were analysed by using inductive analysis instruments to make a conclusion. The conclusion of the research shows that the discourses of Mizan’s books constitute implementation of publisher’s vision and mission, and have significant relation to social setting of religious and politic, so some books that meet socities needs published.